Pelatihan Teknologi Pengolahan Abon dan Serondeng Ikan Patin Pada Kelompok Kewirausahan Mahasiswa FPC Sebagai Cikal Bakal Wirausaha Baru - Suparmi Suparmi; Sumarto Sumarto; Dewita Dewita; Hendro Ekwarso; Santhy W Sidahuruk; Rizky Febriansyah Siregar; Syafrani Syafrani; Ranika Paramita (PELANTAR PRESS, 2023)
UNRI's Faculty of Fisheries and Marine Sciences, which accommodates the field of fisheries from upstream to downstream, seeks to solve the problem of unemployment on campus, especially in the fisheries sector. Through a community service program on entrepreneurship schemes involving lecturers who collaborate with the UNRI Business Incubator Center, we carried out training activities on culinary development based on processed fish with a total of 15 participants, namely FPC students processing fishery products. This training aims to provide entrepreneurial knowledge, encourage the growth of entrepreneurial motivation, and increase understanding of management (organization, production, finance, and marketing) with implementation methods referring to the Participatory Action Learning System(PALS). The implementation of this training activity received a positive response, as did the participants' desire to become entrepreneurs. This training also motivates participants to work as entrepreneurs and opens up job opportunities to collaborate with other small and medium enterprises. The culinary products produced are serondeng catfish and catfish floss. These products have the potential to become a business opportunity for new entrepreneurs.